Association of apolipoprotein b/apolipoprotein a-1 ratio with cardiometabolic risk biomarkers in type 2 diabetes mellitus. - Makaju,Hari Sharan (2021)
ABSTRACT: Background: Patients with Type 2 diabetes mellitus and metabolic syndrome have increased risk for cardiovascular disease (CVD). Metabolic syndrome (MetS) is the collection of cardiometabolic risk factor. Early analysis of cardiometabolic risk reduces the chance of CVD. Apolipoprotein (Apo) B is a crucial structural integral of very low density lipoproteins have, intermediate-density lipoproteins, and low-density lipoproteins. These lipoproteins have atherogenic nature. Apolipoprotein A-I(Apo A-I) is the foremost apolipoprotein associated with high density lipoprotein, and a key initiator and driver of the reverse cholesterol transport. Measuring the ApoB can accurately constituent of antiatherogenic particles whereas ApoA-1 is the major structural constituent of antiatherogenic high-density lipoproteins. Objectives: The aim of this study was to evaluate the association of Apo B/Apo A-I ration with cardiometabolic risk biomarkers in T2DM. Material and Methods: This cross sectional study conducted in Tribhuvan University Teaching Hospital, Kathmandu, included 120 diagnosed with type 2 diabetes mellitus visiting medicine OPD and 120 apparently healthy controls from July 2021 to December 2021. Informed written consent was taken from each participant. All the study Population were classified in line with the NCEP ATP III criteria of MetS. Clinical and anthropometric characteristics were documented using clinical proforma. The fasting blood samples were collected for estimating plasma glucose, traditional lipid profile analysis [Total Cholesterol (TC), Triglyceride (TG), alpha lipoprotein cholesterol (HDL-C)], Apo A-I, Apo B and Hba1C. Serum low-density lipoprotein-cholesterol (LDL-C), very-low density lipoprotein- cholesterol (VLDL-C) and Apo B/Apo A-I ratio were calculated. Comparison of data between the two groups was accomplished by t test. Correlation coefficient of Apo b/ Apo A1 ration with cadiometabolic risk biomarkers were calculated by Pearson's correlation analysis. Results: The mean values of cardiometabolic risk factors like BML, WC, SBP, DBP, FBG, HbA1C, TC, TG, LDL-C, VLDL-C, Non HDL-C, the Apo B and Apo B/Apo A-I ratio in patients with T2DM were significantly higher whereas HDL-C was significantly higher whereas HDL-C was significantly lower than that of a control group (p<_0.001). There was strong positive correlation between the Apo B/Apo A-I ratio and LDL-C, TC, Non HDL-C, and Apo B (r=0.68-0.89, P<0.001). Similarly, modest positive correlation with BMI, WC, TG and VLDL-C(r=0.55-0.67, P<0.001) and a weak, Yet significant, correlation (r=0.18-0.35 p<0.05) with weight, systolic blood pressure and FBG. In contrast, the ration showed negative correlation with HDL-C and Apo A-I (r= -0.58,P<0.001). The prevalence of metabolic syndrome among diabetes mellitus was 77.5%. ROC analysis revealed diagnostic significance of the Apo B/Apo A1 ration for diabetic with MetS. The optimal Apo B/Apo A-I ration cutoff value for detecting diabetic with metabolic syndrome was 0.86 with a sensitivity of 89.2% and specificity of 85.2%. Conclusion: The present study demonstrates that and elevated Apo B/Apo A-I ration constitutes a good association with cardiometabolic biomarkers and supports that the Apo B/Apo A-I ration as a promising risk marker of future cardiovascular disease as it si not interfered by dietary variation of lipid intake during investigation. WC and BMI anthropometric markers can also be rigorously monitored to delay or prevent MetS and consequently the greater risk of CVD. Key Words: Type 2 Diabetes mellitus, metabolic syndrome, Apo B/Apo A-I ratio, cardiometabolic risk factor.